2011
DOI: 10.1159/000324734
|View full text |Cite
|
Sign up to set email alerts
|

Digital Cytology: Current State of the Art and Prospects for the Future

Abstract: The growth of digital methods in pathology is accelerating. Digital images can be used for a variety of applications in cytology, including rapid interpretations, primary diagnosis and second opinions, continuing education and proficiency testing. All of these functions can be performed using small static digital images, real-time dynamic digital microscopy, or whole-slide images. This review will discuss the general principles of digital pathology, its methods and applications to cytologic specimens. As cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 106 publications
0
66
0
2
Order By: Relevance
“…Since high image quality is not sufficient for remote primary cytopathologic diagnosis by itself; microfocusing and whole-slide imaging are also needed. 2,4,5,13 It is not reported that adapters increase the image quality. In the literature, it is stated that image capturing from a microscope ocular with an adapter is easier and faster and the images obtained with an adapter are of standard quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since high image quality is not sufficient for remote primary cytopathologic diagnosis by itself; microfocusing and whole-slide imaging are also needed. 2,4,5,13 It is not reported that adapters increase the image quality. In the literature, it is stated that image capturing from a microscope ocular with an adapter is easier and faster and the images obtained with an adapter are of standard quality.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems have been successfully deployed for case consultation and for rapid cytology evaluations (adequacy assessments). 2,4 Whole Slide Imaging devices scan glass slides with objective similar to those in a light microscope, to create their full digital image. These images can be recorded and evaluated remotely via the Internet.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such a digital transformation in pathology was made possible due to the continuous modernisation of scanning devices, the increasing computers power and the transfer rate coupled with introducing new software solutions and technologies for collecting large amounts of data. One of the important advantages of digital pathology is providing the means to better integrate diagnosis and treatment of cancer by facilitating interaction between multidisciplinary teams of doctors involved in diagnosing and treating these diseases [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%